2021
DOI: 10.1080/10717544.2021.1974606
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: A convergent synthetic platform for dual anticancer drugs functionalized by reduced graphene nanocomposite delivery for hepatocellular cancer

Abstract: Hepatocellular carcinoma (HCC) is widespread cancer with a high degree of morbidity and mortality in individuals worldwide and a serious concern for its resistance to present chemotherapy drugs. In this investigation, the combination of cisplatin (CPT) and metformin (MET) to kill the HepG2 and caco-2 cells was developed into a new pH-responding magnetic nanocomposite based on reduced graphene oxide. Polyhydroxyethyl methacrylic (PHEA) was then linked employing grafting from approach to the reduced graphene oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…5 . These findings align with the work of Amaral et al 67 , who have suggested that p53 triggers apoptosis by activating pro-apoptotic proteins bcl-2-like protein 4 (Bax and Bak) and suppressing anti-apoptotic genes such as BCl2 and surviving, thus activating the caspase pathway 68 .
Figure 5 The gene expression of p53, BCl2, and NF-kB after RGOH100 treatment in cells HepG2.
…”
Section: Resultssupporting
confidence: 92%
“…5 . These findings align with the work of Amaral et al 67 , who have suggested that p53 triggers apoptosis by activating pro-apoptotic proteins bcl-2-like protein 4 (Bax and Bak) and suppressing anti-apoptotic genes such as BCl2 and surviving, thus activating the caspase pathway 68 .
Figure 5 The gene expression of p53, BCl2, and NF-kB after RGOH100 treatment in cells HepG2.
…”
Section: Resultssupporting
confidence: 92%
“…Another evidence of the greater interaction of graphene-based NPs with biological membranes was derived from the confocal microscopy studies: graphene-based nanocarriers comparatively required a longer time to gain access in the HeLa cells, which is a strong indication of its improved interaction with the membrane lipid layer. In the study of nuclear apoptosis of HepG2 cells with stronger internalized Fe 3 O 4 -rGO-based drug NPs, condensed and disintegrated nuclei and chromatin were observed from the apoptotic nuclei at the membrane boundaries . The study on the interaction of GO with mammalian HT-29 cells reveals that GO promotes cell attachment and proliferation .…”
Section: Resultsmentioning
confidence: 96%
“…In the study of nuclear apoptosis of HepG2 cells with stronger internalized Fe 3 O 4 -rGO-based drug NPs, condensed and disintegrated nuclei and chromatin were observed from the apoptotic nuclei at the membrane boundaries. 61 The study on the interaction of GO with mammalian HT-29 cells reveals that GO promotes cell attachment and proliferation. 62 The complex based on the drug−GO−Fe 3 O 4 structure advantageously reduced the viability of HT29 cells in comparison with bare drug−GO NPs and free drug.…”
Section: Resultsmentioning
confidence: 99%
“…They documented that the nanoparticles loaded with metformin/cisplatin exhibited the lowest concentration rate of HepG2 and Caco-2 cells compared to the drug-loaded single nanocomposite groups and free drugs by promoting an apoptotic response. Moreover, Fe3O4@rGO-G-PSEA demonstrated robust effectiveness against tumors in vivo while causing minimal harm to healthy tissues [ 95 ].…”
Section: Preclinical Evidence About Metformin Influence On Hcc Hallmarksmentioning
confidence: 99%